2016
DOI: 10.1099/ijsem.0.001585
|View full text |Cite
|
Sign up to set email alerts
|

List of new names and new combinations previously effectively, but not validly, published

Abstract: The purpose of this announcement is to effect the valid publication of the following effectively published new names and new combinations under the procedure described in the Bacteriological Code (1990 Revision). Authors and other individuals wishing to have new names and/or combinations included in future lists should send an electronic copy of the published paper to the IJSEM Editorial Office for confirmation that all of the other requirements for valid publication have been met. It is also a requirement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…The resulting sequence (accession no. LT615365) showed a 93.2% similarity level with the 16S rRNA gene of Dielma fastidiosa strain JC13, the closest species with a validly published name [30] (Fig. 1).…”
Section: Resultsmentioning
confidence: 95%
“…The resulting sequence (accession no. LT615365) showed a 93.2% similarity level with the 16S rRNA gene of Dielma fastidiosa strain JC13, the closest species with a validly published name [30] (Fig. 1).…”
Section: Resultsmentioning
confidence: 95%
“…However, in the only two publications discussing the taxonomy of Nosocomiicoccus , both groups of authors indicated that it was a member of the Staphylococcaceae [6–8]. Since 2010, four additional genera have been added to the family (listed in order of publication): Aliicoccus [9], Abyssicoccus [10, 11], Corticicoccus [12] and Auricoccus [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mousavi et al (2015) reclassified this species to the genus Allorhizobium , which was included into the Validation list no. 172 of the IJSEM (Oren & Garrity, 2016). Hördt et al (2020) emended a description of All.…”
Section: Discussionmentioning
confidence: 99%